Seasonal and Spatial Variation of PM10 in an Urban Area from Romania - MARIANA CARMELIA BĂLĂNICĂ DRAGOMIR; CRISTIAN MUNTENIȚĂ; ECATERINA DANIELA ZECA; AUREL GABRIEL SIMIONESCU; IRYNA KRAMAR; NATALIIA MARYNENKO (Vasyl Stefanyk Precarpathian National University, 2019)
The cyclic variance of PM10 mass concentration in the urban area in the South-East of Romania has been analysed in the article. SE of Romania is considered to be a territory which has medium level of pollution for a period of last ten years, from 2009 to 2018. The spatial dispersion of PM10 concentration was obtained using the METI-LIS soft wear for each season. The objective of dispersion models is to evaluate how pollutant concentration is spread out taking into account the diffusion. The average measurements of PM10 and meteorological parameters as inputs has been used. An evident seasonal change of PM10 concentrations is observed in the article. In order to establish national measures (including economic ones) for the improvement of the atmospheric pollution control it was analysed the mechanism of atmospheric pollution. It was observed that the air quality was overall better in spring and in summer in comparison to the other two periods. With regard to the seasonal variation characteristics of PM10 significant differences for the air quality registered in different months in the researched region were observed. The impact of air temperature on atmospheric pollution was insignificant in spring and autumn; moreover, precipitation was defined as an important influence factor upon the atmospheric pollution. The impact of precipitation on the possibility of atmospheric pollution was obviously different in the four seasons. The research results indicate the meteorological parameters that influence the air pollution become active during the cold seasonal days. It was shown that relative humidity and wind speed are the meteorological parameters that impact the PM10. It was found out that the probability of atmospheric pollution decreased with the increase of air temperature in summer. The research results also testify that the air pollution mapping could be enhanced using atmospheric dispersion models and in-situ measurements